Health Education about Malaria for the Nabire Community - Talakua, Paulus; Widyowati, Agustin (Universitas STRADA Indonesia, 2024)
Nabire Regency with a total of 1,082 cases. In 2021, there was an increase in malaria cases, reaching 2,456 positive cases of malaria, of which the largest number of cases were in Nabire District with a total of 1,248 positive cases. To reduce the high number of malaria cases, the Nabire Regency Government issued Regent Regulation number 48 of 2019 concerning the Malaria Control Center, but in its implementation there are obstacles faced by the Health Service, namely the lack of community support and the lack of supporting infrastructure in implementing malaria control policies. The aim of community service activities carried out in Nabire Regency is to increase public knowledge and awareness in eradicating malaria. The population of this community service is the Nabire community using counseling methods through community leaders such as village elders, RT, RW and health cadres. The method for solving problems uses several methods and fishbone diagrams. The implementation that has been carried out in this community service is conducting a Forum Group Discussion (FGD) with community leaders consisting of health problems, namely malaria related to community compliance with healthy behavior such as using mosquito nets or installing coarse wire, using mosquito poison, keeping the house clean. After conducting the FGD, we first conducted education regarding malaria prevention through leaflets to community leaders. Health education to the community regarding malaria was assisted by community leaders who participated in the FGD. Community figures who assist in delivering health education are village elders, RT, RW and health cadres. As a result, 85% of community service activities aimed at increasing community knowledge were successful, the community became more knowledgeable about preventing malaria and improving their health. The Conclusion of this research is this community service program was implemented, and resulted in a change in accordance with the output target, namely knowledge about eradicating malaria, especially how to prevent it. It is hoped that the counseling provided can be carried out regularly and applied in people's lives so that the incidence of malaria can decrease.